489. A Case-Control Approach to an Outbreak of SARS-CoV-2 on an Acute Stroke Unit in the U.S. (31st December 2020) - Lesho, Emil P; Walsh, Edward E; Gutowski, Jennifer; Reno, Lisa; Newhart, Donna; Yu, Stephanie; Bress, Jonathan; Bronstein, Melissa
Abstract: Background: Detailed descriptions of hospital-acquired SARS-CoV-2 infections and transmission chains in healthcare settings are crucial to controlling outbreaks and improving patient safety. However, such reports are scarce. We sought to determine origins and factors associated with nosocomial transmission of SARS-CoV-2 in a 528-bed teaching hospital in Western New York. Methods: The index patient, who had mental illness, wandered throughout the ward, would not wear a facemask, and was often kept seated at the nursing station, developed COVID-19 on day- 22 of hospitalization. A case-control approach was used, wherein all patients, staff, and 128 randomly selected environmental surfaces on the outbreak unit (case), and randomly selected patients, staff, and environmental surfaces on designated COVID-19 and non-COVID-19 units (control), were tested for SARS-COV-2 by RT-PCR and IgG SARS-COV-2 antibodies (SAR-Ab). Compliance with hand hygiene (HH) and COVID-specific personal protective equipment (PPE) was assessed. Results: 145 staff and 26 patients were potentially exposed resulting in 25 secondary cases (14 staff and 11 patients). 4/14 (29%) of the staff and 7/11 (64%) of the patients who tested positive, and later became ill, were asymptomatic at the time of testing (Figures 1–2). There was no difference in mean cycle threshold for SARS-COV-2 gene targets between asymptomatic and symptomatic individuals. 0/32 randomly selected staff from the positive and negative control wards tested positive. PPE compliance based on 354 observations was not significantly different between wards. Environmental surface contamination with SARS-COV-2 RNA was not different between outbreak and control wards. Mean monthly HH compliance, based on 20, 146 observations, was lower on the outbreak ward (p < 0.006) (Figure 3). 142 staff volunteered for serologic testing. The proportion staff with detectable SAR-Ab was higher on the outbreak ward (OR 3.78: CI 1.01–14.25). Figure 1 Figure 2 Figure 3 Conclusion: The risk of staff exposure was higher in an outbreak setting than on a dedicated COVID-19 unit (Figure 4). Noncompliant patient behavior, decreased hand hygiene, and pre-symptomatic transmission can contribute to nosocomial spread and are important considerations for ongoing infection control efforts. Figure 4 Disclosures: All Authors : No reported disclosures